Photovoltaic weather-resistant anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof

By using halloysite nanotube coating and maleic anhydride-grafted polyethylene to improve interfacial compatibility in photovoltaic cable materials, the problem of poor water resistance of intumescent flame retardants was solved, resulting in high-efficiency flame retardant, low-smoke, and low-cost photovoltaic cable materials.

CN121086389APending Publication Date: 2025-12-09SICHUAN UNFIRE POLYMER MATERIALS TECH

Patent Information

Application Number
CN202511345903.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing intumescent flame retardants for photovoltaic cable materials have poor water resistance, resulting in poor flame retardant effect. Furthermore, traditional cable materials release a large amount of smoke and toxic gases when burning, affecting mechanical performance and cost.

Method used

Halloysite nanotubes are used as the carbonization framework, and a composite flame retardant is formed through coating treatment. Maleic anhydride-grafted polyethylene is combined to improve interfacial compatibility and dispersibility. Epoxy resin is used to enhance mechanical properties and weather resistance, and ultraviolet absorbers are added to prevent aging.

Benefits of technology

It improves the flame retardancy and water resistance of cable materials, reduces smoke emission, enhances mechanical properties and UV resistance, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of polyolefin cable materials, in particular to a photovoltaic weather-resistant anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material and a preparation method thereof.The photovoltaic weather-resistant anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material is prepared from, by weight, 90-150 parts of polyolefin resin, 1-3 parts of antioxidant, 2-5 parts of ultraviolet light absorber, 30-70 parts of composite flame retardant, 10-25 parts of carbon black and 3-5 parts of cross-linking agent; the composite flame retardant comprises a core material, a first shell material and a second shell material, the core material comprises a halloysite nanotube adsorbed with a flame retardant, the first shell material comprises epoxy resin, and the second shell material comprises maleic anhydride grafted polyethylene. According to the polyolefin cable material provided by the invention, the purpose of efficient flame retardance can be achieved by adding the halloysite nanotubes and the flame retardant system, the interfacial compatibility between the flame retardant and the matrix resin can be improved by adding the maleic anhydride grafted polyethylene, and the flame retardance of the polyolefin cable material can be improved by combining the added halloysite nanotubes and epoxy resin. The purpose of improving weather resistance, stress resistance and crack resistance of matrix resin is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of polyolefin cable material, in particular to a weather-resistant and anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaics and a preparation method thereof. BACKGROUND

[0002] With the rapid development of domestic wire and cable industry and photovoltaic industry, the demand for photovoltaic cable material is increasing. Photovoltaic cables are exposed to harsh outdoor environments (ultraviolet light, high temperature, low temperature, ultraviolet radiation, etc.) for a long time, and their performance directly affects the efficiency and safety of the entire power generation system. Therefore, the cable material needs to have excellent weather resistance, flame retardance, and anti-ultraviolet performance.

[0003] Because traditional cable materials release a large amount of smoke and toxic and harmful gases during combustion, the current mainstream cable material product is low-smoke halogen-free flame-retardant cable material, which has the advantages of less smoke and low toxicity. However, in order to obtain better flame-retardant cable material, a large amount of flame retardant needs to be added to the cable material to meet the requirements, which leads to a decrease in mechanical properties and an increase in cost. In order to overcome the problem of decreased impact strength and easy cracking of the cable material caused by traditional inorganic flame retardants (such as aluminum hydroxide and magnesium hydroxide), one of the solutions is to add an intumescent flame retardant (IFR) system. Specifically, through the synergistic effect of carbon source, gas source, and acid source, a dense and porous intumescent carbon layer is generated during combustion, which can effectively achieve the purposes of heat insulation, oxygen insulation, smoke suppression, and drip prevention. However, the intumescent flame retardant system has poor water resistance due to its strong hygroscopicity, which will destroy the flame-retardant system and reduce the flame-retardant effect. SUMMARY

[0004] The technical problem solved by the present application is: The present application provides a weather-resistant and anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaics and a preparation method thereof, which solves the problem of poor water resistance of the intumescent flame retardant in the prior art.

[0005] The technical solution adopted by the present application is: In a first aspect, the present application provides a weather-resistant and anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaics, wherein the raw materials are as follows: polyolefin resin 90-150 parts, antioxidant 1-3 parts, ultraviolet absorber 2-5 parts, composite flame retardant 30-70 parts, carbon black 10-25 parts, and crosslinking agent 3-5 parts. The composite flame retardant includes a core material, a first shell material, and a second shell material. The core material includes halloysite nanotubes with adsorbed flame retardant, the first shell material includes epoxy resin, and the second shell material includes at least maleic anhydride grafted polyethylene.

[0006] As a preferred embodiment of any of the first aspect of the present application, the polyolefin resin comprises at least one of ethylene-vinyl acetate copolymer, linear low density polyethylene.

[0007] As a preferred embodiment of any of the first aspect of the present application, the antioxidant comprises at least one of antioxidant 1010, antioxidant 168, antioxidant 300.

[0008] As a preferred embodiment of any of the first aspect of the present application, in the composite flame retardant, the flame retardant comprises at least one of ammonium polyphosphate, pentaerythritol, melamine.

[0009] As a preferred embodiment of any of the first aspect of the present application, in the composite flame retardant, the second shell material further comprises a maleic anhydride grafted polyethylene wax.

[0010] As a preferred embodiment of any of the first aspect of the present application, the preparation method of the composite flame retardant comprises the following steps: In the first step, the halloysite nanotube is acidized and silanized to obtain an amino halloysite nanotube. Specifically, the halloysite nanotube is placed in concentrated hydrochloric acid and heated to 70-90℃ for 4-7h, and then cooled to room temperature. After filtration, deionized water washing and drying, the halloysite nanotube is put into a blending solution of APTES and an organic solvent, which is anhydrous ethanol, and reacted at room temperature for 8-16h under stirring. Then, the amino halloysite nanotube is obtained by filtration, deionized water washing and drying. In the foregoing, the mass ratio of the halloysite nanotube, concentrated hydrochloric acid, APTES, and organic solvent is 1:2.5-5:0.5-1:2.5-5.

[0011] In the second step, the amino halloysite nanotube is dispersed in a flame retardant solution, and then subjected to ultrasonic treatment, filtration and drying to obtain a core material. Specifically, the amino halloysite nanotube, ammonium polyphosphate, pentaerythritol and melamine are added to anhydrous ethanol, and then subjected to ultrasonic treatment, filtration and drying to obtain the core material. In the foregoing, the mass ratio of the amino halloysite nanotube, ammonium polyphosphate, pentaerythritol and melamine, and anhydrous ethanol is 100:40-60:15-35:15-35:50-70.

[0012] In the third step, anhydrous ethanol, bisphenol A type epoxy resin (E51), curing agent, core material and sodium dodecyl benzene sulfonate are blended and stirred, and then reacted at 50℃ for 2h. Then, the coated material is obtained by filtration, deionized water washing and drying. In the foregoing, the mass ratio of anhydrous ethanol, bisphenol A type epoxy resin, curing agent, core material and sodium dodecyl benzene sulfonate is 100-130:10:1.5:50-70:0.5.

[0013] Fourthly, the coating, maleic anhydride grafted polyethylene, maleic anhydride grafted polyethylene wax are blended at 300-800 rpm for 5-10 min, and then added into a double-screw extruder for mixing, with an extrusion temperature of 170-230 DEG C and a screw rotation speed of 150-250 rpm, to obtain a composite flame retardant; in the foregoing, the mass ratio of the coating, maleic anhydride grafted polyethylene and maleic anhydride grafted polyethylene wax is 1:0.2:0.1.

[0014] In a second aspect, the present application provides a preparation method of the aforementioned weather-resistant and anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaic, comprising the following steps: The polyolefin resin, antioxidant, ultraviolet absorber, composite flame retardant, carbon black and crosslinking agent are blended at 300-500 rpm for 3-10 min, and then placed in a double-screw extruder for extrusion and granulation, with an extrusion temperature of 150-170 DEG C and a rotation speed of 300-500 rpm, to obtain the polyolefin cable material.

[0015] The technical mechanism and beneficial effects of the present application are as follows: The polyolefin cable material provided by the present application can achieve the purpose of high-efficiency flame retardation by adding halloysite nanotubes and a flame-retardant system, can improve the interfacial compatibility between the flame retardant and the base resin by adding maleic anhydride grafted polyethylene, and can improve the weather resistance, stress resistance and crack resistance of the base resin by adding halloysite nanotubes and epoxy resin, can effectively absorb ultraviolet rays by adding an ultraviolet absorber, thereby achieving the purpose of anti-aging, and can effectively improve the melt flowability of the resin during processing by adding maleic anhydride grafted polyethylene wax.

[0016] The polyolefin cable material provided by the application takes halloysite nanotubes as a carbon skeleton, and is loaded with an intumescent flame retardant system (ammonium polyphosphate, pentaerythritol and melamine), thereby playing a flame-retardant effect. The halloysite nanotubes loaded with the flame retardant are subjected to coating treatment, so as to avoid migration of the flame retardant, thereby improving the water resistance of the flame retardant; the halloysite nanotubes are subjected to amination modification, which is used to adsorb the flame retardant on one hand and can be bonded with the coating layer of epoxy resin on the other hand, thereby improving the coating effect of the flame retardant; meanwhile, the epoxy resin is used as a resin coating layer, the polar groups of which are bonded with the amino groups of the halloysite nanotubes, and the coating layer formed after the epoxy resin is cured is a network structure formed after curing, which can improve the mechanical properties of the matrix resin, and the epoxy resin itself has a certain carbon-forming property, which can synergistically improve the flame-retardant effect with the flame retardant. In addition, the surface of the epoxy resin is coated with maleic anhydride grafted polyethylene, which can solve the problem of poor compatibility of the epoxy resin as the coating layer, and the maleic anhydride grafted polyethylene as the coating layer can avoid agglomeration of the flame retardant, thereby improving the dispersibility; maleic anhydride polyethylene wax is added, which has excellent compatibility with the maleic anhydride grafted polyethylene due to the maleic anhydride groups, and which is also compatible with the matrix resin, while also providing excellent lubricating effect, and since it is a polymer itself, the migration is low. DETAILED DESCRIPTION In order to make the purpose, technical scheme and advantages of the embodiments of the application more clear, the technical scheme in the embodiments of the application will be clearly and completely described below. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments are not specified by the manufacturer, they are all conventional products that can be purchased on the market.

[0017] Embodiment 1 The present embodiment provides a weather-resistant and anti-cracking low-smoke halogen-free flame-retardant polyolefin cable material for photovoltaics, and the raw material components are as follows: Ethylene-vinyl acetate copolymer 75 parts Low-density linear polyethylene 50 parts Antioxidant 1010 2.5 parts Composite flame retardant 60 parts UV-531 3 parts Carbon black 20 parts Triallyl isocyanurate 5 parts In the foregoing, the preparation method of the composite flame retardant is as follows: The first step is to place the halloysite nanotubes in concentrated hydrochloric acid and heat to 90℃ and keep for 5h, after the end of cooling to room temperature, after filtration, deionized water washing, drying, and then put into the mixed solution of APTES and anhydrous ethanol, while in the state of stirring at room temperature for 10h, and then after filtration, deionized water washing, drying to obtain the amino halloysite nanotubes; wherein the mass ratio of halloysite nanotubes, concentrated hydrochloric acid, APTES, anhydrous ethanol is 1:3:0.8:3.

[0018] The second step is to add the amino halloysite nanotubes, ammonium polyphosphate, pentaerythritol, melamine into anhydrous ethanol, and then obtain the core material (halloysite nanotubes adsorbed with flame retardants) through ultrasonic, filtration and drying; wherein the mass ratio of amino halloysite nanotubes, ammonium polyphosphate, pentaerythritol, melamine, anhydrous ethanol is 100:55:25:25:65; ultrasonic: 300W, 1h.

[0019] The third step is to blend the anhydrous ethanol, bisphenol A type epoxy resin, triethylenetetramine, core material, and sodium dodecyl benzene sulfonate under stirring, and then react at 50℃ for 2h, and then obtain the coating material through filtration, deionized water washing and drying; wherein the mass ratio of anhydrous ethanol, bisphenol A type epoxy resin, curing agent, core material, and sodium dodecyl benzene sulfonate is 110:10:1.5:60:0.5.

[0020] The fourth step is to blend the coating material, maleic anhydride grafted polyethylene, and maleic anhydride grafted polyethylene wax at 800rpm for 20min, and then add them into a double-screw extruder for mixing, and the extrusion temperature is 170~230℃, and the screw speed is 150~250rpm, to obtain the composite flame retardant; wherein the mass ratio of coating material, maleic anhydride grafted polyethylene, and maleic anhydride grafted polyethylene wax is 1:0.2:0.1.

[0021] The preparation method of the polyolefin cable material is as follows: blend the ethylene-vinyl acetate copolymer, low-density linear polyethylene, antioxidant 1010, composite flame retardant, UV-531, carbon black, and triallyl isocyanurate at 500rpm for 10min to obtain a blend, and then add the blend into a double-screw extruder for extrusion and granulation, and the extrusion temperature is 150~170℃, and the speed is 300~500rpm, to obtain the polyolefin cable material.

[0022] Comparative Example 1 The difference between the present comparative example and Example 1 is that the composite flame retardant is replaced by halloysite nanotubes adsorbed with flame retardants, maleic anhydride grafted polyethylene, and silicone masterbatch; the halloysite nanotubes are not subjected to acidification and silanization treatment.

[0023] Comparative Example 2 The difference between the present comparative example and Example 1 is that the composite flame retardant is replaced by a coating, maleic anhydride grafted polyethylene and silicone masterbatch.

[0024] Comparative Example 3 The difference between the present comparative example and Example 1 is that the maleic anhydride grafted polyethylene wax is replaced by a silicone masterbatch, and the silicone masterbatch is added into the polyolefin cable material.

[0025] Test Example The cable materials prepared from Example 1 and Comparative Examples 1-4 were used as samples for determination. The melt flow rate was determined according to the method of GB / T 3682.1-2008, the tensile strength and elongation at break were determined according to the method of GB / T 1040.3-2006, the oxygen index was determined according to the method of GB / T 2406.3-2022, and the smoke density was determined according to the method of GB / T 8323.2-2008. The determination results are shown in Table 1.

[0026] Table 1 Determination results of samples

[0027] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. The present application can have various modifications and changes for those skilled in the art. Any modification, equivalent replacement, improvement, etc. within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A weather resistant, anti-cracking, low smoke, halogen free, flame retardant polyolefin cable compound for photovoltaic, characterized in that, The raw material components include, by weight fraction, 90-150 parts of polyolefin resin, 1-3 parts of antioxidant, 2-5 parts of ultraviolet absorber, 30-70 parts of composite flame retardant, 10-25 parts of carbon black, and 3-5 parts of crosslinking agent. The composite flame retardant includes a core material, a first shell material, and a second shell material; the core material includes halloysite nanotubes adsorbed with a flame retardant; the first shell material includes epoxy resin; and the second shell material includes at least maleic anhydride grafted polyethylene.

2. The weathering and cracking resistant low smoke halogen-free flame retardant polyolefin cable compound for photovoltaic applications according to claim 1, characterized in that, The polyolefin resin includes at least one of ethylene-vinyl acetate copolymer and linear low-density polyethylene.

3. The weathering and cracking resistant low smoke and halogen free flame retardant polyolefin cable compound for photovoltaic applications according to claim 1, characterized in that, The antioxidant includes at least one of antioxidant 1010, antioxidant 168, and antioxidant 300.

4. The weathering and cracking resistant low smoke halogen-free flame retardant polyolefin cable compound for photovoltaic applications according to claim 1, characterized in that, The flame retardant includes at least one of ammonium polyphosphate, pentaerythritol, and melamine.

5. The weathering and cracking resistant low smoke and halogen free flame retardant polyolefin cable compound for photovoltaic applications according to claim 1, characterized in that, In the composite flame retardant, the second shell material further includes maleic anhydride grafted polyethylene wax.

6. The weathering and cracking resistant low smoke halogen-free flame retardant polyolefin cable material for photovoltaic according to any one of claims 1 to 5, characterized in that, The preparation method of the composite flame retardant is as follows: In the first step, halloysite nanotubes are treated by acidification and silanization to obtain aminated halloysite nanotubes; In the second step, the aminated halloysite nanotubes are dispersed in a flame retardant solution, and are subjected to ultrasonic treatment, filtration, and drying to obtain halloysite nanotubes adsorbed with a flame retardant; In the third step, anhydrous ethanol, bisphenol A type epoxy resin, curing agent, core material, and sodium dodecyl benzene sulfonate are stirred and blended, and then are subjected to reaction, filtration, deionized water washing, and drying to obtain a coating; In the fourth step, the coating, maleic anhydride grafted polyethylene, and maleic anhydride grafted polyethylene wax are blended, and then are added to a double-screw extruder for mixing to obtain the composite flame retardant.

7. The weathering and cracking resistant low smoke halogen-free flame retardant polyolefin cable compound for photovoltaic applications according to claim 6, characterized in that, The reagent for acidification is concentrated hydrochloric acid, and the reagent for silanization is APTES; the mass ratio of halloysite nanotubes, concentrated hydrochloric acid, APTES, organic solvent is 1:2.5-5:0.5-1:2.5-5.

8. The weathering and cracking resistant low smoke halogen-free flame retardant polyolefin cable compound for photovoltaic applications according to claim 6, characterized in that, The mass ratio of aminated halloysite nanotubes, ammonium polyphosphate, pentaerythritol, melamine, and anhydrous ethanol is 100:40-60:15-35:15-35:50-70.

9. The weathering and cracking resistant low smoke halogen-free flame retardant polyolefin cable compound for photovoltaic applications according to claim 6, characterized in that, The mass ratio of anhydrous ethanol, bisphenol A type epoxy resin, curing agent, core material, and sodium dodecyl benzene sulfonate is 100-130:10:1.5:50-70:0.

5.

10. A process for the preparation of weathering and cracking resistant low smoke halogen free flame retardant polyolefin cable compound for photovoltaic applications as claimed in any of claims 1 to 9, characterized in that, The method includes the following steps: The polyolefin cable material is obtained by blending the polyolefin resin, antioxidant, ultraviolet absorber, composite flame retardant, carbon black, and crosslinking agent at 300-500 rpm for 3-10 min, and then extruding and granulating in a double-screw extruder at an extrusion temperature of 150-170 °C and a rotation speed of 300-500 rpm.

Citation Information

Patent Citations

  • Halogen-free intumescent flame retardant polyolefine cable sheath material and preparation method thereof

    CN103333403A

  • Halloysite nanotube modified ammonium polyphosphate-based flame retardant as well as preparation method and application thereof

    CN113150390A

  • Preparation of polymer composite material from halloysite nanometer tube

    CN1746216A

  • Fire retarding resin composition

    JP2003171569A

Cited By

  • Low-smoke halogen-free flame-retardant polyolefin sheath material and preparation method thereof

    CN122188276A

  • A low-smoke, halogen-free flame-retardant polyolefin sheath material and its preparation method

    CN122188276B